1999
DOI: 10.1099/13500872-145-2-293
|View full text |Cite
|
Sign up to set email alerts
|

Farnesol-induced growth inhibition in Saccharomyces cerevisiae by a cell cycle mechanism

Abstract: The growth of budding yeast, Saccharomyces cerevisiae, was inhibited in medium containing 25 pM farnesol (FOH). The FOH-treated cells were still viable, and were characterized by a transition from budded to unbudded phase as well as a significant loss of intracellular diacylglycerol (DAG). FOH-induced growth inhibition could be effectively prevented by the coaddition of a membrane-permeable DAG analogue which can activate yeast protein kinase C (PKC). However, yeast cell growth was not initiated upon addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 28 publications
4
53
0
1
Order By: Relevance
“…Essentially identical results were obtained when cell division was reversibly arrested by treatment with farnesol (27). As shown in Fig.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Essentially identical results were obtained when cell division was reversibly arrested by treatment with farnesol (27). As shown in Fig.…”
Section: Resultssupporting
confidence: 73%
“…To arrest cell division, cells were treated with 50 M ␣-factor (Zymo Research) or 100 M farnesol (Sigma). This latter treatment arrests cell division by inhibiting DNA ligase and histone acetyltransferase (27).…”
mentioning
confidence: 99%
“…Among the recently identified quorum-sensing molecules is the sesquiterpene alcohol farnesol, which has been shown to affect the morphogenesis and biofilm formation of the yeast C. albicans (21,32). Farnesol is naturally found in essential oils of citrus fruits and was shown to be devoid of toxic effects and nonmutagenic in vitro and in vivo (9,24,26). Farnesol exposure significantly affected the rate of glucan synthesis in S. mutans, the main polysaccharide in the biofilm matrix, and consequently reduced the accumulation and biomass of the biofilms (24).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of farnesol on human cells is particularly relevant in light of reports that subinhibitory concentrations of some antifungal compounds lead to increased production of farnesol by C. albicans (31,59). Machida et al reported that farnesol induces mitochondrion-generated reactive oxygen species and growth arrest in S. cerevisiae yeast cells after a 30-min treatment with farnesol but not after treatment with other isoprenoid compounds (52,53) and have proposed that farnesol inhibits a phosphatidylinositol-type signaling pathway S. cerevisiae (54). Several studies have shown that farnesol may also participate in fungal-bacterial interactions.…”
Section: Multiple Roles Of Autoregulatory Secreted Productsmentioning
confidence: 99%